ANALISA PENURUNAN KUALITAS AIR PADA PENGOPERASIAN KETEL UAP DI MV. NYK VEGA - Andi Wahyu; Dwi Maryuana; Abdi Seno (Dinamika Bahari, 2018)
ABSTRACTSteam boiler is a closed vessel that can produce hot steam with the pressure of more thanone atmosphere by heating the water within it. Water in the process greatly affect thecondition of the kettle, so the quality must always be maintained. The research method used in this research is descriptive qualitative method. The dataanalysis technique used SWOT method to analyze the factors causing the decreasing of waterquality of boiler and the effort made to overcome these factors by identifying the strengths,weaknesses, opportunities, and threats. Based on the result of the research, it can be concluded that water boiler degradation iscaused by: 1) Distilled water not yet widely available on board is caused by leakage ofevaporator pipe on FWG and mechanical seal damage at distillation pump. 2) Freshwaterconditions from land are not eligible for boiler water. To overcome these factors, it isnecessary to check to determine which pipe is leaking, patching the leaking pipe using acopper plug, opening and closing the inlet valve and evaporator outlet slowly to avoidthermal shock, mechanical seal replacement of the distillation pump, and testing the boilerwater , addition of chemical dosing and water boiler blowdown.